Suppressor of Cytokine Signaling 3 in Macrophages Prevents Exacerbated Interleukin-6-Dependent Arginase-1 Activity and Early Permissiveness to Experimental Tuberculosis - Schmok, Erik; Abad Dar, Mahin; Behrends, Jochen; Erdmann, Hanna; Rückerl, Dominik; Endermann, Tanja; Heitmann, Lisa; Hessmann, Manuela; Yoshimura, Akihiko; Rose-John, Stefan; Scheller, Jürgen; Schaible, Ulrich Emil; et al. (Frontiers in Immunology, 2017)
Suppressor of cytokine signaling 3 (SOCS3) is a feedback inhibitor of interleukin (IL)-6 signaling in macrophages. In the absence of this molecule, macrophages become extremely prone to an IL-6-dependent expression of arginase-1 (Arg1) and nitric oxide synthase (NOS)2, the prototype markers for alternative or classical macrophage activation, respectively. Because both enzymes are antipodean macrophage effector molecules in Mycobacterium tuberculosis (Mtb) infection, we assessed the relevance of SOCS3 for macrophage activation during experimental tuberculosis using macrophage-specific SOCS3-deficient (LysMcreSOCS3loxP/loxP) mice. Aerosol infection of LysMcreSOCS3loxP/loxP mice resulted in remarkably higher bacterial loads in infected lungs and exacerbated pulmonary inflammation. This increased susceptibility to Mtb infection was accompanied by enhanced levels of both classical and alternative macrophage activation. However, high arginase-1 (Arg1) expression preceded the increased induction of nitric oxide synthase (NOS)2 and at early time points of infection mycobacteria were mostly found in cells positive for Arg1. This sequential activation of Arg1 and NOS2 expression in LysMcreSOCS3loxP/loxP mice appears to favor the initial replication of Mtb particularly in Arg1-positive cells. Neutralization of IL-6 in Mtb-infected LysMcreSOCS3loxP/loxP mice reduced arginase activity and restored control of mycobacterial replication in LysMcreSOCS3loxP/loxP mice. Our data reveal an unexpected role of SOCS3 during experimental TB: macrophage SOCS3 restrains early expression of Arg1 and helps limit Mtb replication in resident alternatively activated lung macrophages, thereby limiting the growth of mycobacteria. Together, SOCS3 keeps IL-6-dependent divergent macrophage responses such as Nos2 and Arg1 expression under control and safeguard protective macrophage effector mechanisms.